Noncoding RNAs in Tumor Epithelial-to-Mesenchymal Transition. (16th February 2016) - Lin, Ching-Wen; Lin, Pei-Ying; Yang, Pan-Chyr
Abstract : Epithelial-derived tumor cells acquire the capacity for epithelial-to-mesenchymal transition (EMT), which enables them to invade adjacent tissues and/or metastasize to distant organs. Cancer metastasis is the main cause of cancer-related death. Molecular mechanisms involved in the switch from an epithelial phenotype to mesenchymal status are complicated and are controlled by a variety of signaling pathways. Recently, a set of noncoding RNAs (ncRNAs), including miRNAs and long noncoding RNAs (lncRNAs), were found to modulate gene expressions at either transcriptional or posttranscriptional levels. These ncRNAs are involved in EMT through their interplay with EMT-related transcription factors (EMT-TFs) and EMT-associated signaling. Reciprocal regulatory interactions between lncRNAs and miRNAs further increase the complexity of the regulation of gene expression and protein translation. In this review, we discuss recent findings regarding EMT-regulating ncRNAs and their associated signaling pathways involved in cancer progression.